Implementation of the Independent Learning Curriculum and Cognitive Learning Theory at SDN Cileunyi 04 - Asep Abdurahman; Dede Wartini; Asep Nursobah; Mohamad Erihadiana (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum and the application of Cognitivism Learning Theory at SDN Cileunyi 04. A phenomenological approach was employed to explore the direct experiences of the principal, teachers, and students in implementing the curriculum. This qualitative research utilized interviews, observations, and documentation as data collection techniques. Data were analyzed using Miles and Huberman's methods, including data reduction, data presentation, and continuous conclusion drawing. The findings reveal significant progress at SDN Cileunyi 04 in implementing the Merdeka Curriculum, emphasizing student-centered learning and the application of Cognitivism principles. Teachers actively foster innovative teaching strategies, encouraging students to think critically, creatively, and produce tangible outcomes. However, challenges persist, such as limited teacher understanding of the curriculum's philosophy and suboptimal execution of the Strengthening Pancasila Student Profile Project (P5). Proposed solutions include continuous teacher training, leveraging technology for learning, and collaborating with communities and stakeholders to enrich programs. These findings highlight SDN Cileunyi 04's potential to serve as a model of successful curriculum implementation aligned with national education goals.